2022
DOI: 10.1111/arcm.12781
|View full text |Cite
|
Sign up to set email alerts
|

The lifestyles of Bronze Age Zagros highlanders at Deh Dumen, Iran: Insights from midshaft femur cross‐sectional geometry and histology

Abstract: Late Bronze Age multiple human burials from Deh Dumen, Iran, were uncovered in the Zagros Mountains. Using cross‐sectional geometry and histology, a sample (n = 23) of fragmented femora from these burials was examined to test for possible adaptation to transhumant pastoralism. Midshaft femur remodelling and modelling characteristics examined across males, females and age‐at‐death groups partly indicated sex‐specific pastoralist behaviours and possible experiences of walking on rugged terrain in this small samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…Robust femora with evidence for slower remodelling in adulthood has been observed in other anthropological and clinical studies (e.g. Miszkiewicz et al, 2022;Zebaze et al, 2010) because bone will modify its physiological response depending on function (and other factors) throughout the entire human lifespan. So, it is not surprising that bone robusticity markers forming at childhood/adolescence may differ from remodelling markers operating in later decades.…”
Section: Mechanical and Bone Anatomical Constraint Interpretationssupporting
confidence: 53%
See 1 more Smart Citation
“…Robust femora with evidence for slower remodelling in adulthood has been observed in other anthropological and clinical studies (e.g. Miszkiewicz et al, 2022;Zebaze et al, 2010) because bone will modify its physiological response depending on function (and other factors) throughout the entire human lifespan. So, it is not surprising that bone robusticity markers forming at childhood/adolescence may differ from remodelling markers operating in later decades.…”
Section: Mechanical and Bone Anatomical Constraint Interpretationssupporting
confidence: 53%
“…Britz et al, 2009;Burr et al, 1990;Mulhern, 2000;Stout & Lueck, 1995;Miszkiewicz & Mahoney, 2016), respectively, and combined (e.g. Miszkiewicz, 2016;Miszkiewicz et al, 2022; see Supplementary Note 2). Biomechanical loading, amongst other factors (e.g., dietary, hormonal, disease) determines bone (micro)morphology (Heaney, 1995;Heaney et al, 2000;Robling et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This dimensional variability is an indirect reflection of active remodeling of osteons, which truncates old Haversian canals and initiates new ones. This suite of traits is characteristic of cortical bone from a long bone diaphysis of an adult animal undergoing active bone remodeling ( 21 , 22 ). The 2011 genetic and protein sequence data show that the embedded object is mastodon bone ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Haversian canals are passageways for blood vessels and nerves in compact cortical bone, and they lie at the center of the basic unit of cortical bone, the osteon. Critically, osteons (and their central Haversian canals) consistently run in the same direction, parallel to the long bone diaphysis ( 21 , 22 ). The positions and orientations of these canals were then traced in our final digital reconstruction and were consistently parallel ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This paper focuses on the bending stiffness of the tibia. According to CT scanning images ( Figure 1 a), the geometric properties of the cross section of the dense bone of the tibia change linearly, that is, it gradually decreases from the proximal end to the distal end [ 24 , 25 , 26 , 27 ]. Studies found that the second moment of area and inertia change linearly along the tibia.…”
Section: Introductionmentioning
confidence: 99%